YIIFSWA II OPENDAY - YIIFSWA Field Tour - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Farmers and stakeholders on field tour at YIIFSWA II Open Day. YIIFSWA-II showcases High Ratio Propagation Technologies and demonstrates large scale production of early generation seed yam.